The Experiences, Challenges and Acceptance of Online Food Application by the Consumers and the Enhancement of Value Through Blockchain Technology. (September 2021) - Mathur, Purvi; Mathur, Vidhu
Technology has played a role to revolutionise the food delivery service from phone based to online ordering to satiate consumers' ever-shifting demands, making its way to the top. Today, the business of food delivery services is one of the fastest segments of e-commerce. This study is conducted to know how consumer expectations from online food service providers. Customer value creation is the utmost requirement for the sustainability of these services. To create value the bottlenecks need to be removed from the service process to enhance highest quality of customer experience through the application of blockchain technology. This paper studies the relationship between information quality and availability at various levels with customer satisfaction through a technology adoption model and value creation through blockchain.